‘Barangnya ready ya, wal…!’: Language use of Facebook group as a marketing platform - Utomo, Aries; Kuncara, Singgih Daru (CaLLs (Journal of Culture, Arts, Literature, and Linguistics), 2025)
This current study aims to explore language use in Facebook groups as a marketing platform, viewed from linguistic and localized features. It was conducted in a qualitative study by involving two Facebook public groups in Samarinda as the research subjects. In collecting data, observation and documentation of FB’s posts and comments were employed. In analyzing data, it was conducted quantitatively and qualitatively. Based on the findings, it can be summarized that language use in the platform can be categorized within several features, namely: (1) lexical and syntactical features. In lexical features, it was primarily found in reduced forms (6 data), word choice (1 data), and spelling (3 data). In contrast, in syntactical features, it was mostly found capitalization (6 data), grammar (1 data), and punctuation (2 data), (2) localized features found from posts and comments in the two selected FB groups as a marketing place in Samarinda are code-switching (1 data), code-mixing (10 data), lexical borrowing (3 data), and shift (2 data), and (3) Banjar and Java language mainly were employed to communicate in those FB groups beside of using Indonesia language.